Resistance of Escherichia coli Isolated from Water Sources on West Lombok Farms to Antibiotics - Ningtyas, Novarina Sulsia Ista'In; Alfiana Laili Dwi Agustin; Bq. Malikah Hr; Baiq Susdiana Fibrianti (Media Kedokteran Hewan, 2024)
Antibiotics are frequently used arbitrarily in livestock industry without regards for dosage or norms use. The administration of antibiotics to livestock can lead to a decline in their efficacy and contribute to the emergence of antibiotic resistance, hence posing challenges to the quality and safety of livestock products. Escherichia coli (E.coli) is recognized as a bacterial indicator pollution. This study aims to determine the resistance of E. coli to the antibiotic's penicillin G and tetracycline. The study used a survey method with cross-sectional study design in July, 2023 on farms located in West Lombok. Testing was carried out on 10 water samples taken from water sources on farms that showed 2 negative samples and 8 positive samples of E. coli on EMBA media, then continued with resistance tests using Penicillin G and Tetracycline antibiotics by measuring the inhibitory zone that formed. The results of this study showed that E.coli samples experienced resistance to Penicillin G as many as 8 samples and tetracycline as many as 6 samples. E.coli bacteria isolated from drinking water have experienced resistance to antibiotics Penicillin G by 100% and Tetracycline 75%.